Pengaruh Persentase Cabai Patah Terhadap Mutu Fisik dan Laju Respirasi Cabai Merah Keriting (Capsicum annuum L.) Selama Masa Penyimpanan - Dandy Prayoga, Jordan; Mayun Permana, I Dewa Gde; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPA, 2023)
Red curly chili (Capsicum annuum L.) is a commodity that has a high use value for the life of the Indonesian people, but is very susceptible to damage due to fracture while handled in the supply chain system. This is thought to be the main factor that causes a decrease in the shelf life of curly red chili. This study aims to determine the effect of the percentage of fractured chilies on the physical quality and respiration rate of curly red chilies, and also to determine the minimum percentage of fractured chilies that can affect the physical quality and respiration rate of curly red chilies during storage period. The experimental design used in this study was a completely randomized factorial design (CRD-factorial), with the first factor being the percentage of fractured chilies consisting of 0%, 4%, 8%, and 12%, and the second factor being the length of storage time consisting of 0, 2, 4, and 6 days. All treatments were repeated 2 times so that 32 experimental units were obtained. Data were analyzed by analysis of variance (ANOVA) and if the treatment had an effect on the parameters, it was continued with Duncan's Multiple Range Test (DMRT). Parameters observed were weight loss, moisture content, color, texture and respiration rate. The results showed that the interaction between the percentage treatment of fractured chili and storage time had a significant effect on weight loss and respiration rate, and had no significant effect on water content, color, and texture of curly red chili. The minimum percentage of fractured chilies that could have a significant effect on the physical quality and respiration rate of curly red chilies during the storage period was 4%, with a quality that is close to the control treatment until the 4th day of storage which are: 22.36% weight loss; 72.26% water content; 33.1 L* value; 48.3 a* value; 34.1 b* value; 34.08 N texture, and 17.46 mgCO2/kg.hour respiration rate. Keywords: curly red chili, physical quality, respiration rate